KEPEMERINTAHAN KAWASAN METROPOLITAN: SUMBANGAN PEMIKIRAN UNTUK REVISI UU 34/1999 - Teguh Kurniawan (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2006)
Naturally, urban areas are areas that could become country’s important engine ofgrowth especially if the areas are manage adequate and properly. Therefore, it is a big challengefor many countries in managing their urban areas in order to give optimum positivecontributions for their development and in creating cities that livable, comfortable andcompetitive with other cities in the world. In order to be able to find the best way in managingcity, it is undeniable for city’s government to have deeper and better understanding on howother countries managing their cities, especially by implementing governance principles thatinvolving many actors across sectors and regions. This paper tries to describe severalliteratures on how to manage urban areas especially in Metropolitan areas. The paper alsointended to give contribution in revising Law 34/1999 about Governance of Jakarta as SpecialProvince of Indonesian Capital City.